Alterations in Humoral Immunity After Partial Versus Total Tonsillectomy: A Pilot Study and Systematic Review of Literature - Mohamad A Bitar; Charbel Rameh; Nour F Ataya; Alik Najarian; Marita Chakhtoura; Alexander Abdelnoor (Journal of Pediatrics Review, 2016)
Background The palatine tonsils are secondary lymphoid organs, important in sampling antigens directly from the epithelial surfaces. They produce antibodies locally and distally through their migrating B cells.